THE INFLUENCE OF SOCIAL MEDIA MARKETING IN BUILDING TRUSTWORTHINESS AND INTENTION TO DONATE AT CASH WAQF INSTITUTION IN INDONESIA - Ramadlani, Muhammad Afif Rifqi; Abdul Ghani Azmi, Ilhaamie (Online Journal of Islamic Management and Finance (OJIMF), 2024)
This study aims to examines the influence of social media marketing on building trustworthiness of cash waqf institutions (nazhirs of cash waqf) and its mediating effect on the intention to waqf in Indonesia. Conducting a survey approach, data were collected from individuals who have made waqf donations through registered nazhir, which is listed in Badan Wakaf Indonesia (Indonesia Waqf Board) within the last two years. Only individuals who follow nazhir’s social media and have made waqf donation that eligible to participate in this research. The study employs Partial Least Square-Structural Equation Modelling (PLS-SEM) to analyze the relationships of Social Media Marketing (SMM), Nazhir Trustworthiness, and the intention to donate waqf. SMM consists of awareness, informativeness, interactivity, and trendiness. Results from 104 eligible respondents indicate that SMM significantly influences nazhir trustworthiness and intention to waqf in direct path. Furthermore, results also reveal that nazhir trustworthiness plays a role as a partial mediating variable in the relationship between SMM and intention to waqf. The findings suggest that social media marketing is a crucial tool for cash waqf institutions to build trust and encourage waqf contributions, providing valuable insights for policymakers and stakeholders in the waqf sector.